Laboratory Assessment of Coagulation Factor XIII - Schroeder, Verena (Hämostaseologie, 2020)
Laboratory diagnosis of congenital and acquired deficiencies of coagulation factor XIII (FXIII) can be challenging. Determination of FXIII function requires specific and sensitive assays which are not always available. This brief review article summarizes currently used FXIII assay methods, their principles and difficulties, and discusses the recommended diagnostic workup in case of a suspected FXIII deficiency. The article also briefly touches on experimental methods used in FXIII research.
Keywords: coagulation factor XIII; factor XIII assay; FXIII deficiency